Evidence for a fourth locus in Usher syndrome type I. Issue 1 (January 1996) - Gerber, S; Larget-Piet, D; Rozet, J M; Bonneau, D; Mathieu, M; Der Kaloustian, V; Munnich, A; Kaplan, J
Abstract : Usher syndrome type I (US1) is an autosomal recessive condition in which three different genes have been already localised (USH1A, USH1B, and USH1C on chromosomes 14q32, 11q13, and 11p15 respectively). The genetic heterogeneity of US1 has been confirmed in a previous study by linkage analysis of 20 French pedigrees. Here, we report the genetic exclusion of the three previously reported loci in two large multiplex families of Moroccan and Pakistani origin, suggesting the existence of at least a fourth locus in Usher syndrome type I.